Prediction of the side drift force of full ships advancing in waves at low speeds - Liu, Shukui (2020)
In this study, we analyze the experimental results of the mean sway (side drift) forces of six full type ships at low speeds in regular waves of various directions and compare them with numerical results of the in-house 3D panel code NEWDRIFT. It is noted that the mean sway force is most significant in relatively short waves, with the peak being observed at λ/LPP ≈ 0.5–0.6. For λ/LPP > 1.0, the corresponding value is rather small. We also observe a solid recurring pattern of the mean sway force acting on the analyzed full type ships. On this basis, we proceed to approximate the mean sway force with an empirical formula, in which only the main ship particulars and wave parameters are used. Preliminary validation results show that the developed empirical formula, which is readily applicable in practice, can accurately predict the mean sway force acting on a full ship, at both zero and non-zero speeds.